Break the silence. Reinvent the place. Musical Cities to the sound of Brega - Guerra, Paula (Farol, 2024)
Using musical genres such as bregafunk and tecnobrega, we intend to analyze the materialization of the concept of musical cities, along with the link between these musical genres in relation to emerging decolonial perspectives. Concomitantly, and allied to this perspective, we also introduce the concept of techno-vernacular creativity, as a form of artistic-technological agency (GASKINS, 2019) that can be used to describe the ways in which external tools or devices can help marginalized social groups to manifest themselves. Therefore, supported by a methodology of a qualitative nature and socio-historical reflection, our main objective is to analyze the evolution of these two musical genres to date, whilst we intend to embark on an in-depth theoretical-conceptual exploration of the artistic manifestations of the Global South, more specifically in Belém and Pernambuco.